The Effect of Cognitive Integrative Interaction Approach on the Development of Effective Personality of Student Parents - Slimani, Sabrina; Hocine Zidan, Hocine (Journal of Human Sciences, 2020)
The current research aims to reveal the level of active personality, and the impact of a cognitive guidance method in raising the level of active personality among parents through verification of the first hypothesis (there are no statistically significant differences in the ranks of the experimental group degrees before and after the program, the second hypothesis There are no statistically significant differences in the ranks of the control and experimental group in the post-test .The research was based on experimental design, and the researcher adopted the scale (Fayez Ezzeldin Sheldan 2014) with the construction of a guided knowledge program according to the method of interactive analysis, the research sample consisted of ( 20) individuals The results showed that there are indicators of weakness in the effective personality of the parents as well as the impact of the guiding method in achieving the elevation of the active personality through the application of various techniques, to conclude the adoption of a number of recommendations including conducting awareness seminars In schools with parents in order to raise the level of communication and interaction between the school and home, and a number of proposals from them .